2021
DOI: 10.1101/2021.10.29.466448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sub-Cluster Identification through Semi-Supervised Optimization of Rare-cell Silhouettes (SCISSORS) in Single-Cell Sequencing

Abstract: Single-cell RNA-sequencing (scRNA-seq) has enabled the molecular profiling of thousands to millions of cells simultaneously in biologically heterogenous samples. Currently, common practice in scRNA-seq is to determine cell type labels through unsupervised clustering and the examination of cluster-specific genes. However, even small differences in analysis and parameter choice can greatly alter clustering solutions and thus impose great influence on which cell types are identified. Existing methods largely focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…To derive sub- clusters within the macrophage population in an unbiased manner, Louvain cluster analysis was performed using Seurat’s FindCluster function. Specifically, the analysis was performed multiple times with different cluster resolutions (from .2 to 1 in increments of .05), and the cluster result at each resolution was assessed by the Silhouette score [116]. Briefly, Silhouette score evaluates the goodness of clustering by measuring for every cell the similarity with cells in the same cluster as compared to the similarity to cells in other clusters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To derive sub- clusters within the macrophage population in an unbiased manner, Louvain cluster analysis was performed using Seurat’s FindCluster function. Specifically, the analysis was performed multiple times with different cluster resolutions (from .2 to 1 in increments of .05), and the cluster result at each resolution was assessed by the Silhouette score [116]. Briefly, Silhouette score evaluates the goodness of clustering by measuring for every cell the similarity with cells in the same cluster as compared to the similarity to cells in other clusters.…”
Section: Methodsmentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 20, 2022. ; https://doi.org/10.1101/2022.12.20.521178 doi: bioRxiv preprint performed using Seurat's FindCluster function. Specifically, the analysis was performed multiple times with different cluster resolutions (from .2 to 1 in increments of .05), and the cluster result at each resolution was assessed by the Silhouette score [116]. Briefly, Silhouette score evaluates the goodness of clustering by measuring for every cell the similarity with cells in the same cluster as compared to the similarity to cells in other clusters.…”
Section: Integration and Clustering Of Monocytes/macrophages At The T...mentioning
confidence: 99%
“…Therefore, we set out to translate exemplar or marker genes derived from scRNAseq for use in bulk transcriptomics data. We previously showed that the basal-like and classical cell-subpopulation-specific marker genes derived from scRNAseq may be translated to cluster bulk RNAseq of PDAC samples, and highly recapitulated the clinically validated PDAC tumor subtypes 26 . These marker genes were identified using a previously developed tool, SCISSORS, which sensitively identifies rare cell subpopulations as low as 0.092% of the cell population and accurately identifies marker genes of high specificity.…”
Section: Development and External Validation Of Decafmentioning
confidence: 81%
“…SCISSORS includes a carefully designed function, which is a two-step method for the identification of highly cell subpopulation specific genes 26 . Briefly, SCISSORS first derives a candidate gene set by comparing the cell subpopulation of interest to the most related cell subpopulation; then the highly expressed genes from other unrelated cell types are removed from this candidate gene set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation